An interesting new species of Conocephalus (Orthoptera: Tettigoniidae: Conocephalinae) from Argentina - Braun, Holger (Zootaxa, 2022)
Conocephalus cinnamonifrons sp. nov. is distinguished by a cinnamon brown head and a distinctly upcurved ovipositor from South American congeners with usually green heads and practically straight ovipositors. The short-winged species lives in wetlands near the coast of the Río de la Plata, and has also been recorded from Entre Ríos Province. The calling song of the male shows a distinctive pattern of long syllable trains alternating with short sequences of a few isolated syllables, quite different to the songs of the syntopically occurring C. doryphorus and C. longipes. Some ecological aspects are briefly discussed.